Paternalistic Leadership Style and Infrastructure as Determinants of Teacher Performance: The Mediating Effect of Teaching Enthusiasm - Setiawan, Apep; Basrowi; Khaeruman (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2025)
Organizations generally refer to entities or structures that are organized to achieve certain goals. Organizations can be business entities, government agencies, or non-profit organizations that have clear goals and hierarchical structures. One of them is the leadership style applied by the principal. A paternalistic leadership style, which emphasizes a fatherly approach and attention to teacher welfare, can improve teacher motivation and performance. SMK Negeri Kota Cilegon is a State Vocational High School located in the Cilegon City area, Banten. This educational institution is under the auspices of the Education Foundation. Based on the data obtained, the phenomenon of teacher performance at SMK Negeri Kota Cilegon in 2023 was on average in the good category. Therefore, this study aims to fill this gap by providing new insights into how paternalistic leadership and infrastructure influence and contribute to teacher performance through teaching enthusiasm, which is expected to make a significant contribution to academic literature and educational practice using qualititative method. Hypotheses test used partial least square technique. Result Shown to improve teacher performance, schools need to pay more attention to the factors that influence that performance. Although there are several variables in this study that show a positive but insignificant influence, as well as a negative influence that is also insignificant on teacher performance, this should not be ignoredThis can be done through the development of facilities and infrastructure, improving the quality of leadership, and supporting the teaching enthusiasm of teachers.